Assessing Critical Reading Skills of Fifth-Grade Elementary Students in Narrative Text Comprehension - Nurul Faizah; Prana Dwija Iswara; Wahyu Sopandi (Papanda Publisher, 2026)
The proliferation of digital misinformation poses significant challenges for elementary students' information literacy, necessitating robust critical reading skills to evaluate and synthesize textual information effectively. This study systematically assessed the critical reading skills of fifth-grade students in comprehending narrative texts, examining performance across literal, inferential, and evaluative dimensions. A quantitative descriptive design was employed with 34 fifth-grade students (23 males, 11 females) from SDN 1 Sukaresmi, West Bandung Regency, Indonesia. The critical reading assessment, based on Nurhadi's framework and validated through expert review (Cronbach's α = 0.82), measured six primary indicators using narrative texts from government-curated quality reading materials. Data were analyzed using descriptive statistics and comparative analyses. Students demonstrated moderate proficiency in literal comprehension (46.81%) but substantial deficits in higher-order skills, particularly synthesis (35.66%), interpretation of implied meanings (37.01%), and cause-and-effect understanding (34.56%). Female students exhibited marginally higher performance (42.22%) compared to males (38.81%), though differences were not statistically significant. Overall achievement averaged 39.91%, indicating medium-to-low critical reading competency. Critical reading skills among upper elementary students remain underdeveloped, especially in inferential and evaluative domains. These findings underscore the necessity for explicit instructional interventions targeting higher-order comprehension strategies, including scaffolded inference training and causal reasoning instruction, to enhance elementary literacy quality.